Effect of different between-match recovery times on the activity profiles and injury rates of National Rugby League players - Murray, N. B.; Gabbett, T. J.; Chamari, K. (The Journal of Strength and Conditioning Research, 2014)
Professional rugby league competition does not coincide with a standardized amount of recovery between matches; matches can be separated by as many as 10 days and as few as 5 days. These variations in recovery time could influence the match activity profiles and injury rates of players. This study investigated the effect of different between-match recovery times on the activity profiles and injury rates of National Rugby League (NRL) players. Forty-three elite male rugby league players participated in this study. Between-match recovery cycles were defined as short (separated by 5 or 6 days), medium (separated by 7 or 8 days), and long (separated by 9 or 10 days) recovery. Movement was recorded using a commercially available microtechnology unit, which provided information on speed, distance, and repeated high-intensity effort activity. Injuries sustained in either training or match play, which resulted in a missed match, were recorded. Significantly greater (p < 0.05) relative total distance was covered after matches involving short recovery than those involving medium (effect size [ES] = 1.13) or long (ES = 1.08) recovery periods. This difference was because of greater low-speed activity. Injury rates for the adjustables positional group were the highest after short between-match recovery cycles, whereas the injury rates of hit-up forwards and outside backs positional groups were the highest after long between-match recovery cycles. These findings suggest that the activity profiles of NRL match play and the injury rates of specific playing positions are influenced by the amount of recovery between matches. The differences in the activity profiles and injury rates between short, medium, and long between-match recovery cycles should be considered when developing recovery strategies for professional rugby league players.